Al-Af'āl Al-Tsulātsiyah Al-Mazīdah Biharfin wa Fawāiduhā fī Riwāyati Imra'ah Inda Nuqthah Al-Shifr - Rico Fenda Pradana; Nurhidayati Nurhidayati; Luthfi Muhyiddin (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
The problem lies in doing more because the increase comes with new weights and different meanings. It is known that the research from this study analyzes the Al-Af'al Al-Tsulatsiyah Al-Mazidah Biharfin wa Fawaiduha using the corpus linguistic on the on the data source, the novel of a woman at the zero point by Nawal Al-Saadawi. The researcher used the qualitative method in the descriptive analytical study, based on the issues in the discussion, Shigat Al-Af'al Al-Tsulatsiyah Al-Mazidah Biharfin, with a letter that is more frequent, then the benefits and collocation of verbal before and after Al-Af'al Al-Tsulatsiyah Al-Mazidah Biharfin with a letter that is more frequent. The conclusion from this linguistic study is that the Sighat on the weight of “أفعل” is more frequent with the word 30 words on the verb word more frequently than “أصبح” .The researcher found that the collocation “أصبح” more frequent is the Sighat Ism Al-Masdar  as the collocation previously with the number of recurrence 24 repetition  and the Shigat Al-Af'al Al-Tsulatsiyah Al-Mazidah Biharfin as the collocation subsequently with 27 repetition, then the benefit of the Al-Af'al Al-Tsulatsiyah Al-Mazidah Biharfin with a letter that is more frequent for the word “أصبح” is the benefit to indicate the becoming with the number of repetitions 17 times.